2019
DOI: 10.21547/jss.560979
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Local Food on Tourism: Gaziantep Case

Abstract: Experiencing local food in a certain destination becomes one of the most important tourism activities for tourists. Local foods; which play an important role in destination choice, revisit intention and marketing are useful tools for destination development. In 2015 Gaziantep was entitled to join the UNESCO Creative Cities Network in Gastronomy branch. Therefore the aim of this study is to investigate the domestic tourist perception of Gaziantep local food and the effect of this perception on revisit intention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Each group has a different set of behaviors in terms of post-purchase behaviors, re-visit intentions and the perception of their status change caused by their visits to the restaurants. As a result of his study conducted in Gaziantep (Turkey), a part of UNESCO's Creative Cities Network, Sert (2019) found that cultural experience, table manners, variety and taste affect re-visit intentions positively. Both in the destination choices of tourists and their re-visit intentions, local foods were found to have an important role.…”
Section: H1 the Perception Of Gastronomy Tourism Affects Destination ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Each group has a different set of behaviors in terms of post-purchase behaviors, re-visit intentions and the perception of their status change caused by their visits to the restaurants. As a result of his study conducted in Gaziantep (Turkey), a part of UNESCO's Creative Cities Network, Sert (2019) found that cultural experience, table manners, variety and taste affect re-visit intentions positively. Both in the destination choices of tourists and their re-visit intentions, local foods were found to have an important role.…”
Section: H1 the Perception Of Gastronomy Tourism Affects Destination ...mentioning
confidence: 99%
“…Even though some studies defined the key factors in destination satisfaction, there are a few studies analyzing the relative importance of each food-related experience on destination satisfaction (Perez-Galvez et al, 2021a;Cruz et al, 2019;Kivela and Crotts, 2009;LopezGuzman and Sanchez_Canizares, 2012;Björk and Kauppinen-Räisänen, 2014;Hendijani, 2016;López-Guzmán et al, 2017;Björk and Kauppinen-Räisänen, 2017;Erkmen, 2019;Kesici and Çakır, 2020;Dengve Chad, 2011;Perez Galvez et al, 2021). There are also studies conducted to predict the behavioral intentions of tourists (Kivela and Crotts, 2005;Wang, 2015;Chen and Peng, 2018;Leong et al, 2017;Daries et al, 2018;Sert, 2019. ) Many studies on destination satisfaction emphasized the importance of destination satisfaction while making purchasing decisions (Jani and Han, 2014;Hui et al, 2007;Kozak and Rimmington, 2000;Mazursky, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Where traditional food can be an attraction from a place. As expressed by (Sert, 2019) that trying the local food at a destination becomes one of the most important tourism activities for tourists. Because the value of consumption from local food can explain the attitude of tourists towards local food, the image of the food destination, and the behavioral intentions of the tourists (Cho & Kim, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Coğrafi işaretlerin ülkemizdeki kullanımında, her geçen gün tescil edilen ürün sayısının artış göstermesine rağmen, mevcut potansiyelin istenilen oranda işaretlemeye sahip olmadığı görülmektedir (Karaca, 2016: 31). Özellikle yöresel yiyecekleri tadabilmek için bölgeye seyahat eden turistler açısından önemli hale gelen yiyecek içecek sektörü, turistlerin yeniden ziyaret etmelerini sağlayan ve bölgelerin gelişimini destekleyen bir unsur olarak karşımıza çıkmaktadır (Sert, 2019(Sert, :1621. Bölgelere tekrar ziyaret ederek sadık müşteri oluşturmak (Arıkan, Çilesiz ve Arman, 2017: 5) amacıyla turistik deneyim aracı olarak bölgenin gastronomi potansiyelinin kullanılması gerekmektedir (Jong vd., 2018: 144).…”
Section: Introductionunclassified